Analysis on inhibition mechanism of human blood clotting factor-IX by protein from snake venom - Ng, Zhang Jin (School of Bioprocess Engineering, University Malaysia Perlis, 2016)
Blood clotting system played vital roles in preventing excessive bleeding when there was an injury of blood vessel. However, excessive coagulation would lead to some disease, which comprises of strokes, heart attacks and pulmonary embolism. Therefore, the vital roles of anticoagulant could not be ignored in preventing excessive coagulation. This study was undertaken to investigate the molecular interaction to find potential anticoagulant. Besides, this study was carried to evaluate binding events between factor-IX and factor-IX-bp from snake venom, test binding of factor-IX protein in human serum with factor-IX-bp and determine binding abilities of other clotting factors from human blood clotting cascade. The study proved that there was interaction between factor-IX and factor-IX-bp. The optimal concentration of NaCl for aggregation was 250 mM and the optimal size of GNP used was 30 nm. Furthermore, the concentration of 5800 nM of factor-IX was proved to be optimum for aggregation of GNP and at least 100 nM of factor-IX-bp was needed to remove factor-IX from the surface of GNP. In addition, higher concentration of factor-IX-bp was needed to absorb factor-IX from GNP in the presence of serum. Aptamer, was also proved that it could bind to targeted protein (factor-IX) more efficiency as compared to factor-IX-bp. Thrombin was proved that it could not interact with factor-IX and it could not be used as a substitute of factor-IX-bp in the anticoagulation system.